The effects of Selenohomolanthionine supplementation on the rumen eukaryotic diversity of Shaanbei white cashmere wether goats - Longping Li; Lei Qu; Tuo Li (Scientific Reports, 2023)
Abstract Selenium (Se) is an important microelement for animal health. However, the knowledge about the effects of Se supplementation on rumen eukaryotic community remains less explored. In this study, the ruminal eukaryotic diversity in three months old Shaanbei white cashmere wether goats, with body weight (26.18 ± 2.71) kg, fed a basal diet [0.016 mg/kg Se dry matter (DM), control group (CG)] were compared to those animals given basal diet supplemented with different levels of organic Se in the form of Selenohomolanthionine (SeHLan), namely low Se group (LSE, 0.3 mg/kg DM), medium Se group (MSE, 0.6 mg/kg Se DM) and high Se group (HSE, 1.2 mg/kg DM) using 18S rRNA amplicon sequencing. Illumina sequencing generated 2,623,541 reads corresponding to 3123 operational taxonomic units (OTUs). Taxonomic analysis revealed that Eukaryota (77.95%) and Fungi (14.10%) were the dominant eukaryotic kingdom in all samples. The predominant rumen eukaryotic phylum was found to be Ciliophora (92.14%), while fungal phyla were dominated by Ascomycota (40.77%), Basidiomycota (23.77%), Mucoromycota (18.32%) and unidentified_Fungi (13.89%). The dominant eukaryotic genera were found to be Entodinium (55.44%), Ophryoscolex (10.51%) and Polyplastron (10.19%), while the fungal genera were dominanted by Mucor (15.39%), Pichia (9.88%), Aspergillu (8.24%), Malassezia (7.73%) and unidentified_Neocallimastigaceae (7.72%). The relative abundance of eukaryotic genera Ophryoscolex, Enoploplastron and fungal genus Mucor were found to differ significantly among the four treatment groups (P < 0.05). Moreover, Spearman correlation analysis revealed that the ciliate protozoa and fungi were negatively correlated with each other. The results of this study provided newer information about the effects of Se on rumen eukaryotic diversity patterns using 18s rRNA high-throughput sequencing technology.